2019
DOI: 10.25165/j.ijabe.20191205.4922
|View full text |Cite
|
Sign up to set email alerts
|

Visual response effects of western flower thrips manipulated by different light spectr

Abstract: To understand how spectral light wavelength affects thrips visual sensitivity, the selective response and the approach sensitivity of western flower thrips were examined. The results showed that light intensity affected thrips selective sensitivity to different spectra, with good visual sensitivity to blue, ultraviolet (UV), and green light changes to UV, violet, and yellow light when illumination increased from 120 lx to 6000 lx. Red light was the sensitive spectral light driving thrips to respond to sensitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Research on the color vision mechanism and biological characteristics of thrips has shown that thrips have the strongest response in the wavelength range of 500-600 nm, while sunlight intensity, the shape and size of the chromatogram, the background color of the host, and the hanging height all affect the trapping effect of sticky plates [6][7][8][9] . Matteson et al [10] found that the peak value of the retinal potential of F. occidentalis was 545 nm, while the trapping peak value was 524 nm, and therefore presented the irritability of color tropism within a short distance [11,12] .…”
Section: Introduction mentioning
confidence: 99%
“…Research on the color vision mechanism and biological characteristics of thrips has shown that thrips have the strongest response in the wavelength range of 500-600 nm, while sunlight intensity, the shape and size of the chromatogram, the background color of the host, and the hanging height all affect the trapping effect of sticky plates [6][7][8][9] . Matteson et al [10] found that the peak value of the retinal potential of F. occidentalis was 545 nm, while the trapping peak value was 524 nm, and therefore presented the irritability of color tropism within a short distance [11,12] .…”
Section: Introduction mentioning
confidence: 99%
“…UV is an important cue for take‐off flight of thrips (Mazza et al, 2010); however, it is not clear how the attenuating film in our study affected F. occidentalis behaviour. In addition, light intensity can change the response of thrips to spectral wavelengths, as demonstrated in Liu et al (2019). In our study, potentially constricting the spectral range may reduce flower reflection and hence recognition by the thrips and attraction to flowers, preventing dispersal to new egg‐laying sites, but more research is needed to demonstrate this.…”
Section: Discussionmentioning
confidence: 95%
“…Spectral balance is important in insect pest navigation, flight orientation, and food sourcing. Thrips (Thysanoptera) generally have a very restricted range of perception within the UVA (300–400), violet‐blue (401–500), and green‐yellow (501–560) spectra compared with other insect orders (Fennell et al, 2019; Liu et al, 2019; Matteson et al, 1992). UV is an important cue for take‐off flight of thrips (Mazza et al, 2010); however, it is not clear how the attenuating film in our study affected F. occidentalis behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…In the experiment, the visual characteristic state of locusts stimulated by spectral light generated a spectral response amplitude emitted in the visual system (Figure 3), whereas the reaction specificity of the locust visual system absorbing and selecting different spectral light wavelengths and the differences in visual pigments and structures absorbing, refracting, and scattering different light photons [21][22][23][24][25][26][27][28][29] restricted the visual reaction intensity of the locust visual system absorbing different light energy components continuously. This caused a difference in the time-varying physiological regulation of the visual spectrum amplitude emitted in the visual system and characterized by visual reaction intensity.…”
Section: Discussionmentioning
confidence: 99%